The Sequential Introduction of Positive Antecedent and Consequent Components in a Compliance Training Package With Elementary Students. (November 2013) - Bellipanni, Kimberly D.; Tingstrom, Daniel H.; Olmi, D. Joe; Roberts, Dannell S.
We evaluated the separate and combined effects of the antecedent manipulations of effective instruction delivery and time-in, as well as the effects of the addition of the consequent manipulation of contingent praise in a compliance training package for four elementary students displaying low levels of compliance. Four teachers were trained to introduce these components sequentially in multiple baseline across-participants designs for each of two pairs of students. All students increased compliance from below 40% during baseline to between 84% and 96% in the final treatment phase. Support was demonstrated for the separate and independent effects of the positive antecedent components of effective instruction delivery and time-in, when used alone and in combination. The addition of contingent praise either increased compliance slightly or maintained it at already high levels. Treatment integrity and implications for practitioners and school personnel are discussed, including the effectiveness and simplicity of these procedures, while also offering positive, non-coercive approaches to increasing student compliance.